Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) terhadap Hasil Belajar Siswa di Madrasah Aliyah - Mario Sarwo Hadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to determine the effect of the STAD type cooperative learning model on student physics learning outcomes on the Mechanical Wave material in class XI MAN 1 Tanjung Jabung Barat T.P 2019/2020. The research method used is a quasi-experimental with a population of all students of class XI even semester at MAN 1 Tanjung Jabung Barat. The research sample was taken 2 classes determined by random sampling technique, namely Class XI MIA 1 as an experimental class using the STAD type cooperative learning model and class XI MIA 2 as a control class using a conventional learning model. The results showed that the paired-sample t test in the table above obtained a t value of 4.247 > t table 2000 with a significance value of 0.000 < 0.005. In conclusion, there is a significant effect on the use of the STAD type cooperative learning model on student learning outcomes on the subject matter of straight motion in class XI MAN 1 Tanjung Jabung Barat. Keywords: Learning Outcomes, Cooperative Learning Model, STAD